Retiring for the night: how negative attitudes towards ageing can shape expectations and attitudes towards sleep among adults aged 60+ - Serena Salvi; Jennifer Murray; Dilek Önkal; Valerie Egdell (Frontiers in Psychology)
IntroductionNegative attitudes towards ageing are pervasive and can create significant barriers to quality of life and longevity for adults aged 60 and older. Studies indicate that older adults with negative views of ageing often perceive common, treatable ailments as a natural consequence of age, impacting their health-seeking behaviours, such as good sleep hygiene. Little is known about how these ageing attitudes shape beliefs about sleep in older adults.MethodsThis study examined the association between attitudes towards ageing and beliefs about sleep in older adults, using data collected through online surveys. Measures included the Pittsburgh Sleep Quality Index, the Centre for Epidemiologic Studies Depression Scale, and the Brief Ageing Perceptions Questionnaire. Hierarchical regression analysis was applied to assess the predictive relationships among these variables.ResultsEmotional responses to ageing, such as worry and frustration, were strongly associated with dysfunctional sleep beliefs, explaining additional variance in sleep beliefs even after controlling for demographic factors, depressive symptoms, and sleep quality. Control-related perceptions of ageing predicted locus of control for sleep, with positive beliefs associated with an internal locus of control and negative beliefs linked to an external locus of control.ConclusionFindings suggest that perceptions of ageing significantly influence attitudes towards sleep, potentially affecting health-seeking behaviours. Addressing age-related stereotypes and fostering positive attitudes may reduce barriers to healthcare engagement and encourage healthier sleep behaviours in older adults, thereby supporting better mental and physical well-being. This study highlights the importance of tackling ageing stereotypes to promote healthier ageing.